(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The authors have conducted the analysis of the legislation of Ukraine, the case law of Ukraine and the European Court of Human Rights, as well as doctrinal approaches to understanding legitimate expectations as objects of corporate legal relations. It has been concluded that the share (capital share), and in fact participation in the company, is an asset associated with the occurrence of favorable property consequences in the future, and has all the characteristics of legitimate expectations. Participation in a company has all the characteristics necessary for its potential monetary evaluation, because it is negative from its owner (does not have a personal, inseparable connection with the person to whom it belongs), and therefore is potentially viable. Monetary evaluation of the participation in the company allows us to classify this object as property benefits (asset). The emergence of economic benefits, as a result of the use of participation, the exercise of the right to it, indicates the connection of such benefits with the consequences that arise. Thus, participation in the company has all the characteristics of legitimate expectations. That is, the participant expects in the future to receive economic benefits from the participation in the company (exercise of corporate rights) that result from the placement of certain values in the charter capital, which have a monetary value. Legitimate expectations, in addition to regulatory corporate legal relations, can be recognized as the object of protective corporate relations, based on the facts of the violation of the right to peaceful possession of such property. It is applied both to the violation of the right to manage the corporation (in case of failure to notify about the general meeting of participants) and the refusal to repurchase shares from a shareholder as the exercise of the “right to disagree”. It is alleged that there are also protective legal relations with such an object as legitimate expectations in case of the violation of the rights to dividends, to the payment of the value of the share (capital share), to the liquidation quota. But such legal relations are not corporate, because the rights to be protected are not included into the group of corporate rights.